Ledakan Populasi Jenis Respo, Filicaulis bleekeri, di Sentra Produksi Sayur Rejang Lebong, Bengkulu - Dwinardi Apriyanto; B. Toha; I. Manti (Jurnal Perlindungan Tanaman Indonesia, 2003)
During the last two years a slug species, Filicaulis bleekeri (Keferst.), has become important pest of some vegetable crops in vegetable production central Rejang Lebong,Bengkulu. This pest is called "respo" by local farmers, who majority are Javanese. Data from preliminary observation indicated that this pest population was very high and may caused harvest failure on some vegetable crops, particularly Cruciferae such as cabbage, chinese cabbage, and cauliflower. In several sampling activities in 2000 and 2001, the population density of respo reached >10 per mature cabbage plant and >7 per flowered cauliflower plant. Sampling on young cabbage and chinese cabbage resulted >2 respo per 1 m of row, but killed >80% of transplanted cabbage and 75% of transplanted chinese cabbage. Whereas sampling in fallow land resulted >60 respo per m2. There is no much information on this pest presently; therefore it is necessary to study the biology as well technology and as control strategy of the species.